2022
DOI: 10.3389/fphar.2022.1030173
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine in liver diseases: Pharmacology and toxicology

Abstract: We have previously shown that adenosine A1AR antagonists, adenosine A2aAR antagonists, and caffeine have significant inhibitory effects on the activation and proliferation of hepatic stellate cells in alcoholic liver fibrosis. Many recent studies have found that moderate coffee consumption is beneficial for various liver diseases. The main active ingredient of coffee is caffeine, which is a natural non-selective adenosine receptor antagonist. Moreover, numerous preclinical epidemiological studies and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…These findings complement an existing body of literature describing the roles of A 2A receptors in fibrogenesis (Herman‐de‐Sousa et al, 2022; Kim et al, 2022; Perez‐Aso et al, 2014; Shaikh et al, 2016; J. Zhang et al, 2017) and the effects of caffeine on tissue fibrosis. For instance, caffeine has been reported to inhibit the activation of BHK‐21 kidney fibroblasts induced by hypoxia (Nilnumkhum et al, 2019) and it has also been reported to attenuate fibrosis of the liver (Modi et al, 2010; Shan et al, 2022) and lungs (Tatler et al, 2016). Conversely, however, caffeine worsened fibrosis in a mouse model of cystic kidney disease (Meca et al, 2019), activation of A 2A receptors attenuated fibrosis in experimental glomerulonephritis (Garcia et al, 2011), and a dual‐acting A 2A receptor agonist and A 3A receptor antagonist (LJ‐4459) reduced tubulointerstitial fibrosis in UUO mice (Pak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings complement an existing body of literature describing the roles of A 2A receptors in fibrogenesis (Herman‐de‐Sousa et al, 2022; Kim et al, 2022; Perez‐Aso et al, 2014; Shaikh et al, 2016; J. Zhang et al, 2017) and the effects of caffeine on tissue fibrosis. For instance, caffeine has been reported to inhibit the activation of BHK‐21 kidney fibroblasts induced by hypoxia (Nilnumkhum et al, 2019) and it has also been reported to attenuate fibrosis of the liver (Modi et al, 2010; Shan et al, 2022) and lungs (Tatler et al, 2016). Conversely, however, caffeine worsened fibrosis in a mouse model of cystic kidney disease (Meca et al, 2019), activation of A 2A receptors attenuated fibrosis in experimental glomerulonephritis (Garcia et al, 2011), and a dual‐acting A 2A receptor agonist and A 3A receptor antagonist (LJ‐4459) reduced tubulointerstitial fibrosis in UUO mice (Pak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al, 2017) and the effects of caffeine on tissue fibrosis. For instance, caffeine has been reported to inhibit the activation of BHK-21 kidney fibroblasts induced by hypoxia (Nilnumkhum et al, 2019) and it has also been reported to attenuate fibrosis of the liver (Modi et al, 2010;Shan et al, 2022) and lungs (Tatler et al, 2016).…”
mentioning
confidence: 99%
“…Moderate coffee intake has been suggested to have beneficial effects (hepatoprotective effect) on various liver diseases, including alcoholic liver disease, 50 nonalcoholic fatty liver disease, 51,52 liver cirrhosis, 53 hepatitis caused by hepatitis B virus, 54 and hepatitis C virus, 55 possibly by inhibiting the binding of adenosine to its receptor. 56,57 Furthermore, espresso coffee has been shown to have no beneficial effect on liver disease, particularly nonalcoholic fatty liver disease. 58 This may be due to the effect of the addition of sucrose, which is composed of glucose and fructose, to the coffee, which may counteract the effect.…”
Section: Commonly Accepted Concepts and Actual Examples About The Cof...mentioning
confidence: 99%
“…Caffeine, which belongs to the methylxanthines family, exhibits dose‐dependent desirable effects at lower doses (≤400 mg), but shows adverse effects and health issues across multiple organ systems at concentrations higher than this dose of ingestion (Lopes et al, 2019; Shan et al, 2022). Thus, several mechanisms have been suggested for the caffeine pharmacological impact on various organs and systems, including antioxidant and anti‐inflammatory activities; some of the elucidated mechanisms or pathways adopted by caffeine to exhibit therapeutic potency in different diseases of the same organ via different receptors or pathways are also briefed in Table 2.…”
Section: Organ‐specific Physiological Consequences Of Caffeinementioning
confidence: 99%